Revisiting the genotypes of Theileria equi based on the V4 hypervariable region of the 18S rRNA gene - Nehra, Anil Kumar; Kumari, Ansu; Moudgil, Aman Dev; Vohra, Sukhdeep (Frontiers in Veterinary Science, 2024)
Introduction Equine theileriosis, an economically important disease that affects horses and other equids worldwide, is caused by a tick-borne intracellular apicomplexan protozoa Theileria equi. Genotyping of T. equi based on the 18S rRNA gene revealed the presence of two, three, four or five genotypes. In previous published reports, these genotypes have been labelled either alphabetically or numerically, and there is no uniformity in naming of these genotypes. The present study was aimed to revisit the phylogeny, genetic diversity and geographical distribution of T. equi based on the nucleotide sequences of the V4 hypervariable region of the 18S rRNA gene available in the nucleotide databases. Methods Out of 14792 nucleotide sequences of T. equi available in the GenBank™, only 736 sequences of T. equi containing the complete V4 hypervariable region of the 18S rRNA gene (>207 bp) were used in multiple sequence alignment. Subsequently, a maximum likelihood phylogenetic tree was constructed based on the Kimura 2-parameter model (K2+I). Results The phylogenetic tree placed all the sequences into four distinct clades with high bootstrap values which were designated as T. equi clades/ genotypes A, B, C and D. Our results indicated that the genotype B of Nagore et al. and genotype E of Qablan et al. together formed the clade B with a high bootstrap value (95%). Furthermore, all the genotypes probably originated from clade B, which was the most dominant genotype (52.85%) followed by clades A (27.58%), and C (9.78%) and D (9.78%). Genotype C manifested a comparatively higher genetic diversity (91.0-100% identity) followed by genotypes A (93.2-99.5%), and B and D (95.7-100%). The alignment report of the consensus nucleotide sequences of the V4 hypervariable region of the 18S rRNA gene of four T. equi genotypes (A-D) revealed significant variations in one region, between nucleotide positions 113-183, and 41 molecular signatures were recognized. As far as geographical distribution is concerned, genotypes A and C exhibited far-extending geographical distribution involving 31 and 13 countries of the Asian, African, European, North American and South American continents, respectively. On the contrary, the genotypes B and D exemplified limited distribution with confinement to 21 and 12 countries of Asian, African and European continents, respectively. Interestingly, genotypes A and C have been reported from only two continents, viz., North and South America. It was observed that genotypes A and C, and B and D exhibit similar geographical distribution. Discussion The present study indicated the presence of only four previously described T. equi genotypes (A, B, C and D) after performing the molecular analyses of all available sequences of the complete V4 hypervariable region of the 18S rRNA gene of T. equi isolates in the GenBank™.